Biotech cementitious materials: Some aspects of an innovative approach for concrete with enhanced durability - Pacheco-Torgal, F.
The deterioration of reinforced concrete structures is a very common problem due to the fact that this material has a high permeability which allows water and other aggressive media to enter, thus leading to corrosion problems. The use of sealers is a common way of contributing to concrete durability. However, the most common ones are based on organic polymers which have some degree of toxicity. The Regulation (EU) 305/2011 related to the Construction Products Regulation emphasizes the need to reduce hazardous substances. Therefore, new low toxicity forms to increase concrete durability are needed. Recent investigations in the field of biotechnology show the potential of bioinspired materials in the development of low toxic solutions. This paper reviews current knowledge on the use of bacteria for concrete with enhanced durability. It covers the use of bacteria in concrete mix and also biomineralization in concrete surface treatments. Investigation gaps are described. Results from practical applications in which there is exposure to environmental conditions are still needed in order to confirm the importance of this new approach. (C) 2012 Elsevier Ltd. All rights reserved.